(untitled) (Journal of the College of Basic Education, 2023)
The aim of the research is to find out the effect of the exploratory method by playing on the achievement of primary school students in mathematics.To achieve the goal, the following hypothesis was put forward:- There is a statistically significant difference at the level of significance (0.05) between the mean scores of the fifth grade primary students in the achievement test of the experimental group (who will study according to the exploratory method by playing) and the control group (who will study according to the usual method).The research sample was selected from fifth grade primary school students at Abdul Karim Qasim Primary School for Boys in the second semester of the academic year (2011-2012). It consisted of (64) students, and by random appointment, Division (B) was chosen to represent the experimental group with (32) students and divisions. (C) The control group was represented by (32) students. The two groups were rewarded in (chronological age, previous achievement in mathematics, previous information in mathematics).(23) teaching plans were prepared for each of the experimental and control groups, and an achievement test consisting of (30) items was prepared after the end of the experiment. The data were processed using appropriate statistical methods, including (T-test for two independent samples, and the Kweder-Richardson equation 20).